Constellation shaping in high-speed optical fiber communications - Tiago Gonçalves Marques da Cunha (2021)
The use of Probabilistic Constellation Shaping is investigated in this work combined with ASK modulation with a distribution matcher, causing a non equal symbol probability. For the Distribution Matcher a Constant Composition Distribution Matcher is used. Channel adaptation is achieved by using several error correcting codes with different code rates and by changing the symbol probability in the transmitter. In the receiver, the Belief Propagation Algorithm is used with LDPC codes from DVB-S2 with code rates (3/4,4/5,5/6,8/9,9/10). Two different channels are simulated, one dominated exclusively by white Gaussian noise and the other by a channel simulated fiber optics in MATLAB. The system is analysed at a BER < 10−4.